Predictive value of neutrophil-lymphocyte ratio in assessing the outcomes of diabetic foot ulcer - Zia Ur Rehman,; Shaikh, Hafsa; Bachani, Filza (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the correlation of neutrophil-lymphocyte ratio with clinical outcomes in diabetic foot ulcer cases. Method: The retrospective, cross-sectional, single-centre study was conducted at Section of Vascular Surgery, Aga Khan University Hospital, Karachi (Pakistan), and comprised data from January 2019 to January 2022 of diabetic foot inpatients of either gender aged at least 18 years. Un-hospital complications and outcomes were noted along with other data on a self-designed proforma. Diagnostic performance of neutrophil-lymphocyte ratio and its correlation with qualitative variables were assessed. Data was analysed using SPSS 26. Results: Of the 130 patients with mean age 60.13+/-11.75 years, 98(75.4%) were males. Surgical intervention was needed in 118(90.8%) cases, with below-knee amputation being the most frequent procedure 38(32.3%). Neutrophil-lymphocyte ratio >4 was significantly associated with a higher grade of diabetic foot ulcer, major amputation, and postoperative complications (p<0.0001) as well as with in-hospital (p=0.008) and 1-year mortality (p=0.01). Conclusion: Neutrophil-lymphocyte ratio could be potentially used as a sensitive and economically feasible biomarker for evaluating the prognosis of patients presenting with diabetic foot ulcers. Key Words: Diabetic foot, Outcomes, Complications, Surgery.